(untitled) (Clinics, 2013)
OBJECTIVES: Bladder cancer represents 3% of all carcinomas in the Brazilian population and ranks second in incidence among urological tumors, after prostate cancer. The loss of p53 function is the main genetic alteration related to the development of high-grade muscle-invasive disease. Prima-1 is a small molecule that restores tumor suppressor function to mutant p53 and induces cancer cell death in various cancer types. Our aim was to investigate the ability of Prima-1 to induce apoptosis after DNA damage in bladder cancer cell lines. METHOD: The therapeutic effect of Prima-1 was studied in two bladder cancer cell lines: T24, which is characterized by a p53 mutation, and RT4, which is the wild-type for the p53 gene. Morphological features of apoptosis induced by p53, including mitochondrial membrane potential changes and the expression of thirteen genes involved in apoptosis, were assessed by microscopic observation and quantitative real-time PCR (qRT-PCR). RESULTS: Prima-1 was able to reactivate p53 function in the T24 (p53 mt) bladder cancer cell line and promote apoptosis via the induction of Bax and Puma expression, activation of the caspase cascade and disruption of the mitochondrial membrane in a BAK-independent manner. CONCLUSION: Prima-1 is able to restore the transcriptional activity of p53. Experimental studies in vivo may be conducted to test this molecule as a new therapeutic agent for urothelial carcinomas of the bladder, which characteristically harbor p53 mutations.